Money-making investments : your broker doesn't tell you about - Maturi, Richard J. (Chicago : Probus, 1994)
This book will give you a firm foundation on alternative investment options which can provide greater diversification and stability to your portfolio. Diversification ranks as a key element in the successful investment equation and there's a wide range of theories and strategies on how to achieve this which are discussed in this book.
Includes index.
aia 8/9/16
Loans
Keywords: Investments; Finance, Personal; United States